Immunoregulatory Aspects of Immunotherapy 2018
DOI: 10.5772/intechopen.75143
|View full text |Cite
|
Sign up to set email alerts
|

Serological Biomarkers for the Prediction and Detection of Human Papillomavirus Associated Cancers

Abstract: High-risk human papillomavirus (HPV) types are not only associated to uterine cervical cancer, but also to a fraction of cancers of the vulva, vagina, penis, anus, head and neck. An HPV infection generates a protective humoral immune response against the capsid proteins L1 and L2; however, an immune response against other HPV early proteins is also generated. This latter is not a protective response, but those antibodies can be useful as biomarkers of the status of the infection and/or the stage of the cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 139 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…If such a test could be incorporated into population screening using point‐of‐care testing of appropriately aged nonvaccinated women (e.g., 30–65 years as recommended by cervical screening guidelines), 44 it would improve screening rates, reduce losses to follow‐up (people, samples, and results) and ultimately lead to early detection of the disease in limited‐resource settings. Individuals who have been seropositive to both HPV E6/E7 antibodies are at higher risk for cervical cancer, 45 which makes them potentially useful biomarker candidates for early detection of cervical cancer 46 . However, we found that evidence is still limited for HPV antibodies to be translated into an effective detection tool for cervical cancer detection.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…If such a test could be incorporated into population screening using point‐of‐care testing of appropriately aged nonvaccinated women (e.g., 30–65 years as recommended by cervical screening guidelines), 44 it would improve screening rates, reduce losses to follow‐up (people, samples, and results) and ultimately lead to early detection of the disease in limited‐resource settings. Individuals who have been seropositive to both HPV E6/E7 antibodies are at higher risk for cervical cancer, 45 which makes them potentially useful biomarker candidates for early detection of cervical cancer 46 . However, we found that evidence is still limited for HPV antibodies to be translated into an effective detection tool for cervical cancer detection.…”
Section: Discussionmentioning
confidence: 83%
“…Individuals who have been seropositive to both HPV E6/E7 antibodies are at higher risk for cervical cancer, 45 which makes them potentially useful biomarker candidates for early detection of cervical cancer. 46 However, we found that evidence is still limited for HPV antibodies to be translated into an effective detection tool for cervical cancer detection. Further laboratory studies are required on the development of more accurate HPV serological biomarkers for them to be successfully translated into an effective screening or point‐of‐care detection tool for cervical cancer.…”
Section: Discussionmentioning
confidence: 90%